Cps 1-Complaint Economic Dispatch for a Single Balancing Authority System Including Ramp Rate - Chavez-Orostica, H (Institute of Electrical and Electronics Engineers Inc., 2016)
Various formulations have consider the compliance of control performance standards into account. In terms of secondary frequency control, it is necessary to perform second-by-second, several moths long simulations of system frequency that most commercial software cannot perform. This paper presents a model framework to simulate frequency control dynamics over periods of time of the order of months, considering frequency dynamics and economic dispatch. An Economic Dispatch formulation that ensures CPS1 compliance in a single balancing authority scenario is simulated, and an explanatory dynamic simulation is presented. © 2016 IEEE.